Perpendicular dowel-bearing strength properties without glue line for Mengkulang species / Nor Jihan Abd Malek … [et al.] - Abd Malek, Nor Jihan; Hassan, Rohana; Raja Hussin, Tengku Anita; Ng, Dick Tern; Adam, Constantine (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
The aim of this project is generate connection data that can employed in the design of connections for Malaysian timber species particularly for glulam products. This investigation focuses on evaluating dowel-bearing strength for timber based products. Thus far, limited studies on dowel-bearing strength were published and reported. Mengkulang, (Heritiera spp), was used to evaluate the dowel-bearing strength properties, Two bolt diameters 16 and 20mm consecutively were selected in this study. The project comprised experimental work that was based ASTMD5 764, using half-hole testing setup. The dowel-bearing strength, Fₑ for 16mm and 20mm diameter were determined from 5% diameter offset yield load method. Through the experimental work and analysis, the percentage difference between 16mm and 20mm was found 15% increased from 16.24N/mm² to 19.2 IN/mm², respectively. The dowel-bearing strength increased when the dowel diameter increased. The comparison between dowel-bearing strength of 5% diameter offset load, Fₑ and maximum load, Fh of glulam without glue line has successfully analysed. The Fe and Fh was found 16.24 N/mm² and 18.50N/ mm² for the 16 mm diameter while was 19.2 IN/ mm² and 22.69 N/ mm² for the 20mm diameter respectively.